2007
DOI: 10.1016/j.ijrobp.2006.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Interfractional Variations in Lung Tumor Position Using Respiratory Gated and Ungated Megavoltage Cone-Beam Computed Tomography

Abstract: Purpose/Objective-To evaluate the use of megavoltage cone-beam CT (MV CBCT) to measure interfractional variation in lung tumor position.Materials/Methods-Eight non-small-cell lung cancer patients participated in the study, 4 nongated and 4 using respiratory gating. All patients received a MV CBCT scan at weekly intervals. Contoured planning CT and MV CBCT images were spatially registered based on vertebral anatomy, and displacements of the tumor center of mass (COM) determined. Setup error was assessed by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 45 publications
2
34
0
1
Order By: Relevance
“…Studies with deformable analytical 14 and physical 18 phantom provide a known ground truth for comparison. The second means of validation is a patient imaging study, in which patients will receive an additional CBCT gated at end expiration 6 that acts as a bronze standard for comparison to the motion-corrected CBCT. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with deformable analytical 14 and physical 18 phantom provide a known ground truth for comparison. The second means of validation is a patient imaging study, in which patients will receive an additional CBCT gated at end expiration 6 that acts as a bronze standard for comparison to the motion-corrected CBCT. …”
Section: Discussionmentioning
confidence: 99%
“…We have investigated gated CBCT to reduce motion artifacts. 6 A limitation is the low duty cycle for imaging ͑20%-30%͒, resulting in correspondingly longer ͑4-5 min͒ acquisition times.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier study has shown that interfractional variations in lung tumor position relative to the skeletal anatomy do occur in this patient group, and that correction of systematic error in tumor position may improve treatment accuracy. 13 A second study goal is to examine whether explicit measurement of tumor respiratory motion trajectories is important to tumor localization, by comparing registration of respiration-correlated image sets to that of respiration-averaged images. Tools for acquiring respirationaveraged images are more widely available and rigid registration of respiration-averaged CT and CBCT images is a wellestablished and time-efficient procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of interfractional variations in lung tumor position using megavoltage CBCT, systematic deviations were comparable or larger than random ones, suggesting that using volumetric imaging for correction of systematic error could be an efficient and effective means of improving treatment accuracy. 13 A particular challenge in thoracic disease sites is that respiratory motion can introduce artifacts in a planning CT scan and blur in a CBCT, thus reducing localization accuracy. Respiration-correlated CT (RCCT), where images are retrospectively binned according to the respiratory phase, has been shown to reduce respiratory motion artifacts and yield 3D images at different points in the respiratory cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a margin around the target would be unnecessary, except in disease site with intra-fraction uncertainties. The complexity of IGRT-D is compounded at sites that experience motion*most commonly due to respiration [79]. Yet, respiratory control and IGRT-D are distinct processes and one does not imply the other.…”
Section: Dose Delivery Assurancementioning
confidence: 99%